2022
DOI: 10.1097/phm.0000000000002056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Perceived Physical and Mental Health and Healthy Lifestyle Behaviors of People with Disabilities: Quantitative Analysis of the International Community Survey

Abstract: ObjectiveThis study aims to determine the perceived impact of the coronavirus pandemic on physical and mental health and healthy lifestyle behaviors in community-dwelling persons with disabilities, as compared with those without disabilities.DesignA prospective cross-sectional study was conducted with a web-based global survey.ResultsOver 3 mos, 3550 responses were collected from 65 countries. The study included 2689 responses without skipped questions as full data for analysis. Most respondents were women (82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This was similar to the primary study by Tuakli-Wosornu et al ( 14 ), which observed that 61.37% of participants were not disabled, 69.58% had mild to moderate disability, and 75% had severe disability and reported deterioration in their mental health. Another report from South Korea by Tuakli-Wosornu et al revealed that 65% of South Korean respondents with and without disabilities had worsening mental status.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was similar to the primary study by Tuakli-Wosornu et al ( 14 ), which observed that 61.37% of participants were not disabled, 69.58% had mild to moderate disability, and 75% had severe disability and reported deterioration in their mental health. Another report from South Korea by Tuakli-Wosornu et al revealed that 65% of South Korean respondents with and without disabilities had worsening mental status.…”
Section: Discussionsupporting
confidence: 90%
“…Self-perceived physical health change in Qatar worsened in 43.4% of individuals without disabilities and 52% of those with disabilities. Tuakli-Wosornu et al primary study ( 14 ) reported that 40% of the participants were not disabled, 48.3% had mild to moderate disability, and 56% had severe disability and reported deterioration in their physical health. In our study, 58% of individuals without disabilities and 47% of persons with disabilities exercised 2–4 days/week, it is slightly better than that in the primary study where 41% (with and without disabilities) exercised at the same frequency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Healthy behavior, including physical activities, sleep, and diet, is the general name of various activities for people to strengthen the body system and maintain physical and mental health ( 55 ). As one of the most positive forms of physical activity ( 56 ), physical exercise can not only promote individuals' physical ( 57 ) and mental health ( 58 ) but also makes people realize the important role of healthy behavior ( 59 , 60 ) during the pandemic. Some colleges and universities took health courses and sports activities as auxiliary means as adjust means to adjust the physical and mental state of college students during campus lockdown ( 61 , 62 ) so as help them pursue a healthy life and promote the occurrence of preventive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In a study with 2,689 people, represented by 65 countries, the negative impact of the pandemic on the state of physical and mental health, as well as on lifestyle (eating habits, sleep, and tobacco use) was evidenced, with worse results for those who were severely deficient in health status (Tuakli-Wosornu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%